2011
DOI: 10.1002/cncr.25939
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase (CYP19) promoter gene polymorphism and risk of nonviral hepatitis‐related hepatocellular carcinoma

Abstract: BACKGROUND: Experimental studies suggest that sex hormones may induce or promote the development of hepatocellular carcinoma (HCC). Androgens are converted to estrogens by the CYP19 gene product, aromatase. Hepatic aromatase level and activity have been shown to be markedly elevated in HCC. Aromatase expression in liver tumors is driven by a promoter upstream of CYP19 exon I.6. METHODS: First, the authors identified an A/C polymorphism in the exon I.6 promoter of the CYP19 gene. To determine whether allelic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Exon I.6 has been shown to act as a repressor element of exon PII, and its transcriptional activity decreased when the C allele of rs10459592 was present. 16,32 The C-A haplotype may reduce CYP19 expression by reducing the transcriptional activity of exon I.6 and enhancing its activity as a repressor of the exon PII promoter, although the effect of the C-A haplotype on PII was only marginal in the present study. However, because the fold change of the effect of the haplotype was quite modest, further precise analyses will be required to conclude that the SNPs directly affect circulating or microenvironmental sex hormone levels.…”
Section: Controlcontrasting
confidence: 65%
See 1 more Smart Citation
“…Exon I.6 has been shown to act as a repressor element of exon PII, and its transcriptional activity decreased when the C allele of rs10459592 was present. 16,32 The C-A haplotype may reduce CYP19 expression by reducing the transcriptional activity of exon I.6 and enhancing its activity as a repressor of the exon PII promoter, although the effect of the C-A haplotype on PII was only marginal in the present study. However, because the fold change of the effect of the haplotype was quite modest, further precise analyses will be required to conclude that the SNPs directly affect circulating or microenvironmental sex hormone levels.…”
Section: Controlcontrasting
confidence: 65%
“…The rs10459592 and rs4775936 SNPs are located 21 and 142 bp downstream of the exon I.6 promoter, respectively. Exon I.6 has been shown to act as a repressor element of exon PII, and its transcriptional activity decreased when the C allele of rs10459592 was present . The C‐A haplotype may reduce CYP19 expression by reducing the transcriptional activity of exon I.6 and enhancing its activity as a repressor of the exon PII promoter, although the effect of the C‐A haplotype on PII was only marginal in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al [13] demonstrated that aromatase exon 1b could not be detected in fibrolamellar HCCs. Aromatase promoter exon I.6 in HCC was reported to be detected by several investigators [35,50]. These findings all indicated that the aromatase exon 1 utilization patterns may be changed by neoplastic transformation of hepatocytes themselves.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, prostaglandin E2 and cytokines, such as IL-6 or TNFa, were also reported to regulate CYP19A1 expression and aromatase activity [6,22,23]. Therefore, the intrahepatic level of aromatase may be reasonably postulated to be influenced by that of the factors above, which is different among several types of inflammatory or neoplastic disease such as hepatitis, cirrhosis, steatosis, HCC, and MLC [35]. However, in our present study, no significant aromatase immunoreactivity was detected in the adjacent normal hepatocytes with possible exceptions of HCC and MLC.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the SNPs are within 200 bp of transcription factor binding sites and would be predicted to have an effect on transcriptional regulation (Table 5). The SNP in the CYP19A1 gene is located within a Fos–Jun site and has been shown to impact transcriptional activity – the C allele had 60% higher promoter activity than the A allele (30). Growth rate in GHD was lower in TT homozygotes, implying that lower aromatase activity would associate with poorer growth responses.…”
Section: Discussionmentioning
confidence: 99%